BEBERAPA FAKTOR YANG TERKAIT DENGAN KEJADIAN INFEKSI NOSOKOMIAL LUKA OPERASI DI RSUD KOTA SEMARANG TAHUN 2OO3 - Devi . Fitriyastantir; M. . Sulchan; Sayono . . (Universitas Muhammadiyah Semarang, 2003)
ABSTRACT Backgrounds: nosocomial infection causes the losing of mater, longer medication duration, decreasing of productivity, also decreasing of hospital's quality. It is necessary to be investigated about the determinant factor of nosocomial Infection. Problem of research : what factors is just which related to the happening of hurt operate for infections Nosocomial in RSUD Town Semarang? Objectives: to analyze the correlations among the age, gender, wound treatment category, duration of post operation treatment, usage of prophylactic antibiotic, wound size, and level of room treatment with the prevalence of nosocomial infection. Research Methods this explanatory research used cross sectional design and approach. The independent variables are (l) age, (2) gender, (3) wound treatment category, @) duration of post operation treatment, (5) usage of prophylactic antibiotic, (6) wound size, (7) level of room treatment, and the dependent variable is Prevalence of nosocomial infection. Result: there are 7 cases of 88 patients with surgery wound. They are 4 of 50 males patients and 3 of 38 females. There are significant correlations among age, wound treatment category. Durations of post surgery treatment, usage of prophylactic antibiotic, and level of room treatment with the prevalence of nosocomial Infection ( p < 0,05). Conclusions: There are significant correlation among age, wound treatment category, duration of post surgery treatments, usage of prophylactic antibiotic, and level of room treatment with the prevalence of nosocomial Infection Keyword: surgery wound, nosocomial infection, prophylactic antibiotic